2018
DOI: 10.3775/jie.97.186
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tin Nanoparticles by Pulse Discharge in Water and Aqueous Gelatin Solution

Abstract: High-voltage pulse discharges were generated between underwater two metallic Tin (Sn) wires in order to synthesize nanoparticles. Nanoparticles were synthesized in pure water or aqueous gelatin solution. In pure water, Sn and SnO 2 particles of approximately 5 nm in diameter were synthesized. However, synthetic particles in pure water had a problem of aggregation. The influence of gelatin solution on the particle size and dispersibility of the synthetic particles was investigated. In 10 mg/L gelatin aqueous so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In their study, methanol played a role in inhibiting the aggregation of PtPd nanoparticles. Table 5 briefly summarizes SP-prepared metal materials [68,71,111,[113][114][115][116][117][118][119][120][121][122][123]. Au…”
Section: Carbon Materialsmentioning
confidence: 99%
“…In their study, methanol played a role in inhibiting the aggregation of PtPd nanoparticles. Table 5 briefly summarizes SP-prepared metal materials [68,71,111,[113][114][115][116][117][118][119][120][121][122][123]. Au…”
Section: Carbon Materialsmentioning
confidence: 99%
“…The same group [126] suggested that adding CTAB only changes the growth pattern of Ta2O5 crystallites rather than influencing the composition of Ta2O5 nanoparticles using the same process. Musaka et al [52] demonstrated that the average diameter of tin nanoparticles produced by wire erosion was non-linearly dependent on the concentration of gelatin, used as a surfactant in water, with a minimum value at 2 mg/L. Although the observed behavior is not fully understood, it may be attributed to an optimal activation of gelatin by the discharge for a certain production rate of tin.…”
Section: Surfactantsmentioning
confidence: 99%
“…This avoids the use of a feedback loop consisting of an electrode-gap detector and an analog electronic unit as controller to permanently adjust the position of one electrode in relation to the other to set the desired gap distance, as in [141]. For example, considering a tungsten wire with a diameter of 1 mm and an erosion rate of 100 mg h −1 , the eroded length after 1 h is 0.9 mm (as shown in [52]). However, the coaxial alignment of pin and coil becomes crucial to operating the system for long periods of time.…”
Section: Gap Distancementioning
confidence: 99%